2008
DOI: 10.1038/sj.mt.6300382
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Design for Multiple shRNA Expression and Durable HIV-1 Inhibition

Abstract: Human immunodeficiency virus type 1 (HIV-1) replication in T cells can be inhibited by RNA interference (RNAi) through short hairpin RNA (shRNA) expression from a lentiviral vector. However, for the development of a durable RNAi-based gene therapy against HIV-1, multiple shRNAs need to be expressed simultaneously in order to avoid viral escape. In this study, we tested a multiple shRNA expression strategy for different shRNAs using repeated promoters in a lentiviral vector. Although highly effective in co-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
233
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(247 citation statements)
references
References 48 publications
10
233
1
3
Order By: Relevance
“…Several viruses have been engineered to efficiently deliver genetic cargos into mammalian cells (4). Retro-and lentiviruses are not ideal due to their highly recombinogenic single-stranded RNA genome (5). In fact, a recent attempt to develop a lentiviral vector for UAA mutagenesis in mammalian cells was limited to a single tRNA expression cassette, and required multiple vectors to deliver all of the required genetic elements, significantly compromising its efficiency and utility (6).…”
Section: Resultsmentioning
confidence: 99%
“…Several viruses have been engineered to efficiently deliver genetic cargos into mammalian cells (4). Retro-and lentiviruses are not ideal due to their highly recombinogenic single-stranded RNA genome (5). In fact, a recent attempt to develop a lentiviral vector for UAA mutagenesis in mammalian cells was limited to a single tRNA expression cassette, and required multiple vectors to deliver all of the required genetic elements, significantly compromising its efficiency and utility (6).…”
Section: Resultsmentioning
confidence: 99%
“…However, care must be taken to space each shRNA-expression cassette because the simple combination of the expression cassettes and the repeat sequence may result in reduced activity of each shRNA or even deletion of some shRNA. 47 …”
Section: Discussionmentioning
confidence: 99%
“…22,23 The multiple shRNA strategy has been investigated in the context of human immunodeficiency virus-1 treatment and shown to successfully overcome viral escape and mutation. 24,25 For example, Brake et al 26 showed that human immunodeficiency virus-1 could escape from a single shRNA attack but not from four shRNAs that were simultaneously expressed in a cell. A multiple shRNA strategy was also used to silence hepatitis C or B virus and superior inhibition of viral replication was observed.…”
Section: Introductionmentioning
confidence: 99%
“…As REs usually require addition of a minimal CMV promoter to achieve high expression levels, we substituted the CMV promoter-driving DsRed with the hPGK promoter to avoid the potential of homologous recombination due to repeated sequences, as previously reported for lentiviral vectors. 29 We also replaced EGFP with ZsG-DR, a brighter and destabilized (t 1/2 ¼ 8 --12 h) green fluorescent protein to better capture the kinetics of gene expression. Finally, we cloned the promoter for the well-known early myogenic marker, aSMA upstream of ZsG-DR, to monitor smooth muscle cell maturation in response to TGF-b1 treatment.…”
Section: Generation Of Shlvdp Vectormentioning
confidence: 99%